An experimental study on hydrodynamic process, beach profile, and sand migration in swash zone under action of dam-break bore. (December 2022) - Deng, B.; Zhang, W.; Tang, H.S.; Jiang, C.B.; Liu, X.J.
Abstract: This study makes an experimental study on hydrodynamics and sediment driven by dam-break waves in swash zones of three sandy beaches. The experiment adopts three beaches: a 1:10 uniform-sand beach, a 1:10 non-uniform-sand beach, and a 1:35 non-uniform-sand beach. This paper reports its measurements on swash water depth, morphology, bedload, and migration of sand particles. It also analyzes the hydraulic jump and sandbar, sorting and sedimentology characteristics, and fractal dimension of bedform. The analysis indicates that the uniformness of sand particle sizes plays an important role in hydrodynamic behaviors, bedform evolution, bedload transport, and migration of sand particles. The fractal dimension of beach profiles lies between 1.15 and 1.25 after swash action, despite changes in bed profiles.